West Bank Water Department. Institutional reform towards national bulk supply utility - Jaas M. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
West Bank Water Department (WBWD) is the official governmental body turned by the Israeli Civil Administration to a sort of public department, with responsibilities of operating and maintaining bulk water facilities. A presentation will be made about the background of the WBWD, the creation of the National Water Utility (NWU), its objective and mandate. A summary will be made of the institutional legal aspects, capacity building/ organization and the different suggested forms of the NWU. As conclusion, a review will be made about the achievements in regard of the creation of the NWU.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)